The Extended Leibniz Rule and Related Equations in the Space of Rapidly Decreasing Functions - König, Hermann; Milman, Vitali (Журнал математической физики, анализа, геометрии, 2018)
We solve the extended Leibniz rule T(f•g)=Tf•Ag+Af•Tg for operators T and A in the space of rapidly decreasing functions in both cases of complex and real-valued functions. Ми розв язуємо узагальнене правило Лейбниця T(f•g)=Tf•Ag+Af•Tg для операторiв T та A у просторi швидко спадних функцiй, як у випадку комплекснозначних функцiй, так i у випадку дiйснозначних функцiй.